Antioxidant Carbon Nanoparticles Inhibit Fibroblast-Like Synoviocyte Invasiveness and Reduce Disease Severity in a Rat Model of Rheumatoid Arthritis - Mark R. Tanner; Redwan Huq; William K. A. Sikkema; Lizanne G. Nilewski; Nejla Yosef; Cody Schmitt; Carlos P. Flores-Suarez; Arielle Raugh; Teresina Laragione; Pércio S. Gulko; James M. Tour; Christine Beeton (MDPI AG, 2020)
Reactive oxygen species have been involved in the pathogenesis of rheumatoid arthritis (RA). Our goal was to determine the effects of selectively scavenging superoxide (O2•−) and hydroxyl radicals with antioxidant nanoparticles, called poly(ethylene glycol)-functionalized hydrophilic carbon clusters (PEG-HCCs), on the pathogenic functions of fibroblast-like synoviocytes (FLS) from patients with rheumatoid arthritis (RA) and on the progression of an animal model of RA. We used human FLS from patients with RA to determine PEG-HCC internalization and effects on FLS cytotoxicity, invasiveness, proliferation, and production of proteases. We used the pristane-induced arthritis (PIA) rat model of RA to assess the benefits of PEG-HCCs on reducing disease severity. PEG-HCCs were internalized by RA-FLS, reduced their intracellular O2•−, and reduced multiple measures of their pathogenicity in vitro, including proliferation and invasion. In PIA, PEG-HCCs caused a 65% reduction in disease severity, as measured by a standardized scoring system of paw inflammation and caused a significant reduction in bone and tissue damage, and circulating rheumatoid factor. PEG-HCCs did not induce lymphopenia during PIA. Our study demonstrated a role for O2•− and hydroxyl radicals in the pathogenesis of a rat model of RA and showed efficacy of PEG-HCCs in treating a rat model of RA.